Fronto‐cerebellar dysfunction and dysconnectivity underlying cognition in friedreich ataxia: The IMAGE‐FRDA study. Issue 1 (27th October 2015) - Harding, Ian H.; Corben, Louise A.; Storey, Elsdon; Egan, Gary F.; Stagnitti, Monique R.; Poudel, Govinda R.; Delatycki, Martin B.; Georgiou‐Karistianis, Nellie
Abstract: Friedreich ataxia (FRDA) is a progressive neurodegenerative disorder defined by pathology within the cerebellum and spinal tracts. Although FRDA is most readily linked to motor and sensory dysfunctions, reported impairments in working memory and executive functions indicate that abnormalities may also extend to associations regions of the cerebral cortex and/or cerebello‐cerebral interactions. To test this hypothesis, 29 individuals with genetically confirmed FRDA and 34 healthy controls performed a verbal n ‐back working memory task while undergoing functional magnetic resonance imaging. No significant group differences were evident in task performance. However, individuals with FRDA had deficits in brain activations both in the lateral cerebellar hemispheres, principally encompassing lobule VI, and the prefrontal cortex, including regions of the anterior insular and rostrolateral prefrontal cortices. Functional connectivity between these brain regions was also impaired, supporting a putative link between primary cerebellar dysfunction and subsequent cerebral abnormalities. Disease severity and genetic markers of disease liability were correlated specifically with cerebellar dysfunction, while correlations between behavioural performance and both cerebral activations and cerebello‐cerebral connectivity were observed in controls, but not in the FRDA cohort. Taken together, these findings support a diaschisis model of brain dysfunction, whereby primary disease effects in the cerebellum result in functional changes in downstream fronto‐cerebellar networks. These fronto‐cerebellar disturbances provide a putative biological basis for the nonmotor symptoms observed in FRDA, and reflect the consequence of localized cerebellar pathology to distributed brain function underlying higher‐order cognition. Hum Brain Mapp 37:338–350, 2016 . ©2015 Wiley Periodicals, Inc.